Outcomes of left atrial appendage occlusion using the AtriClip device: a systematic review. (10th July 2019) - Toale, Conor; Fitzmaurice, Gerard J; Eaton, Donna; Lyne, Jonathan; Redmond, Karen C
Abstract: Atrial fibrillation increases lifetime stroke risk. The left atrial appendage (LAA) is thought to be the source of embolic strokes in up to 90% of cases, and occlusion of the LAA may be safer than the alternative of oral anticoagulation. Occlusion devices, such as the AtriClip TM (AtriCure, Mason, OH, USA) enable safe and reproducible epicardial clipping of the LAA. A systematic review was performed in May 2018, based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines, using the keyword 'AtriClip'. A total of 68 papers were identified and reviewed; 11 studies were included. Data including demographics, medical history intervention(s) performed, periprocedural outcomes and follow-up were assessed and analysed. A total of 922 patients were identified. LAA occlusion was achieved in 902 out of 922 patients (97.8%). No device-related adverse events were reported across the studies. The reported incidence of stroke or transient ischaemic attack post-clip placement ranged from 0.2 to 1.5/100 patient-years. Four hundred and seventy-seven of 798 patients (59.7%) had ceased anticoagulation on follow-up. The AtriClip device is safe and effective in the management of patients with atrial fibrillation, either as an adjunct in patients undergoing cardiac surgery or as a stand-alone thoracoscopic procedure.